Differences in VO2max measurements between breath-by-breath and mixing-chamber mode in the COSMED K5 - Winkert, K.; Kirsten, J.; Kamnig, R.; Steinacker, J. M.; Treff, G. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Automated metabolic analyzers are frequently utilized to measure maximal oxygen consumption (VO2max). However, in portable devices, the results may be influenced by the analyzer`s technological approach, being either breath-by-breath (BBB) or dynamic micro mixing chamber mode (DMC). The portable metabolic analyzer K5 (COSMED, Rome, Italy) provides both technologies within one device, and the authors aimed to evaluate differences in VO2max between modes in endurance athletes.